Determination of healthy natural antioxidants in selected muskmelon (Cucumis melo) cultivars - IMEN, HENANE; ANISSA, RIAHI; IMEN, TLILI; CHAFIK, HDIDER (The Indian Journal of Agricultural Sciences, 2023)
Muskmelon (Cucumis melo L.) is a popular summer fruit consumed all over the world due to the combination ofrefreshingly sweet taste, pleasant flavour and nutritional value. Melon fruit is characterized by germplasm variabilitywith superior quality. This study aimed to evaluate 5 promising local muskmelon cultivars (Maazoun, Galaoui,Stambouli, Trabelsi, Asli) for some physicochemical characteristics, the content of different bioactive compoundsand the antioxidant activity. The experiments were conducted for two consecutive years 2018 and 2019 at the support station of the inter-professional vegetable group positioned in the North East of Tunisia. Significant differences were observed across the melon cultivars (P